Multidrug Resistant Acinetobacter - Manchanda, Vikas (Medknow Publications, 2010)
Emergence and spread of Acinetobacter species, resistant to most of the available antimicrobial agents, is an area of great concern. It is now being frequently associated with healthcare associated infections. Literature was searched at PUBMED, Google Scholar, and Cochrane Library, using the terms ‘Acinetobacter Resistance, multidrug resistant (MDR), Antimicrobial Therapy, Outbreak, Colistin, Tigecycline, AmpC enzymes, and carbapenemases in various combinations. The terms such as MDR, Extensively Drug Resistant (XDR), and Pan Drug Resistant (PDR) have been used in published literature with varied definitions, leading to confusion in the correlation of data from various studies. In this review various mechanisms of resistance in the Acinetobacter species have been discussed. The review also probes upon the current therapeutic options, including combination therapies available to treat infections due to resistant Acinetobacter species in adults as well as children. There is an urgent need to enforce infection control measures and antimicrobial stewardship programs to prevent the further spread of these resistant Acinetobacter species and to delay the emergence of increased resistance in the bacteria.